1995
DOI: 10.1099/0022-1317-76-8-1971
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of promoter function in human and animal cells infected with human recombinant adenoviruses expressing rotavirus antigen VP7sc

Abstract: ) promoter and a modified Ad major late promoter were best, functioning equally well but with different kinetics. In other human cell lines the CMV promoter was more versatile, generally providing sustained expression at a significant level, in one case for at least 6 days. In addition, as mouse, rabbit and pig models of rotavirus infection are under investigation and VP7sc is a vaccine antigen, we also investigated the ability of the recombinant adenoviruses to infect cells from these and other sources. VP7sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
3
11
1
Order By: Relevance
“…HCMV promoter strength was intermediate between that of MCMV and MLP, except in rat fibroblasts where neither MLP nor HCMV elicited production of elafin mRNA or protein. These results highlight the observation that cells which cannot support replication of viruses (A549 cells and fibroblasts) exhibit differences in promoter efficiency as noticed previously by Xu et al 17 For example, in keeping with Xu et al's study in Hela cells, we found that MLP was a poor promoter compared with HCMV in A549 cells ( Figure 2 and Table 1).…”
Section: Figure 3 Anti-human Neutrophil Elastase (Hne) Activity Of Cosupporting
confidence: 92%
See 1 more Smart Citation
“…HCMV promoter strength was intermediate between that of MCMV and MLP, except in rat fibroblasts where neither MLP nor HCMV elicited production of elafin mRNA or protein. These results highlight the observation that cells which cannot support replication of viruses (A549 cells and fibroblasts) exhibit differences in promoter efficiency as noticed previously by Xu et al 17 For example, in keeping with Xu et al's study in Hela cells, we found that MLP was a poor promoter compared with HCMV in A549 cells ( Figure 2 and Table 1).…”
Section: Figure 3 Anti-human Neutrophil Elastase (Hne) Activity Of Cosupporting
confidence: 92%
“…Expression may also depend on the reporter gene itself since we found that in A549 cells, elafin expression is driven more efficiently by HCMV than MLP, a pattern different from that observed for the expression of VP7sc by Xu et al 17 The biological activity of adenovirus-derived elafin was confirmed in that conditioned medium from A549 cells infected with Ad5-MCMV-EL inhibited HNE in a dose-dependent fashion (Figure 3). Furthermore, biological activity of elafin was further demonstrated by the resistance of A549 cells transfected with Ad5-MCMV-EL to HNE-induced damage (unpublished data).…”
Section: Figure 3 Anti-human Neutrophil Elastase (Hne) Activity Of Comentioning
confidence: 52%
“…parallel to the direction of E1 transcription) expressed higher levels of protein. Xu et al (1995), noted the same orientation dependence using E1 replacement Ad vectors expressing rotavirus antigen VP7sc regulated by the 0n4 kb HCMV IE promoter or the Ad 2 major late promoter. This effect may be due, in part, to the presence of the E1a enhancer which remains in the vector backbone.…”
Section: Discussionmentioning
confidence: 78%
“…Most antisense VEGF studies have relied on the human CMV promoter, which is widely used in the ®eld of gene transfer, to drive antisense RNA expression. However, despite the advantages of promoter strength, gene expression from the CMV promoter is often transient in nature, varies between different cell types and is potentially suppressed when used in conjunction with adenovirus vectors (Xu et al, 1995;Clesham et al, 1996;Guo et al, 1996;Stinski, 1999). Other promoters that have been successfully used to express antisense RNA, are the RNA polymerase III group of promoters, which include the adenovirus VAI RNA gene (Cagnon et al, 1995;Good et al, 1997).…”
Section: Discussionmentioning
confidence: 96%